Identification of Ecological Factors Influencing Students’ Leisure Time - Kamali, Zahra; Esmaili, Mohammad Reza; Zarei , Ali (Assessment and Practice in Educational Sciences, 2026)
Sport and the environment are closely interconnected. Sport is regarded as a tool for achieving the principles of sustainable development. The more ecologically optimal and standardized the urban sport spaces are, the more citizens’ physical and mental health will be ensured without concern. The aim of the present study was to identify the ecological factors influencing students’ leisure time. In terms of purpose, the study is applied research, and methodologically, it is a qualitative inquiry conducted using Glaser’s unstructured grounded theory approach. The statistical population consisted of faculty members who were experts in the field of students’ leisure time. In this study, the views of 14 experts were collected through purposive sampling via semi-structured interviews until theoretical saturation was achieved. The reliability of the interviews, using the intra-subject agreement method, was obtained as 0.75. For data analysis, the constant comparative method was applied through three stages of open, axial, and selective coding using MAXQDA software (version 2018). In the open-coding stage, 109 codes were extracted, and in the axial-coding stage, 9 categories were obtained. Ultimately, seven factors—(infrastructural facilities, environmental, social factors, cultural development, sport-environment services, aesthetic aspects, and accessibility)—were identified as key ecological factors. Therefore, authorities must pay special attention to their critical responsibility, which is to implement optimal planning aligned with the interests of the younger generation while preserving societal values.